Sosialisasi Sosialisasi Sistem Hidroponik Kepada Siswa SMA YPN Noling Kabupaten Luwu: Pendahuluan - Anwar; Syarif, Muhammad Munawir (Window of Community Dedication Journal, 2020)
Hydroponics is one method of plant propagation without using soil media which is still unfamiliar in the area. Therefore it is deemed necessary to socialize and introduce it to the community through high school students, in the hope that it can be used as a hobby and even a new business field. The problems faced by partner groups are still lack of socialization about the hydroponic system of public schools, and they do not have technical skills for hydroponic cultivation. In terms of the many advantages offered by the hydroponic system, such as ease in plant care, controlling the levels of nutrients needed by plants, where nutrition can be provided according to needs. In addition, the hydroponic vegetable yields are crisp and fresher. Based on the results of evaluation and monitoring after the socialization was quite satisfactory. Because this is only the socialization stage so this PKM activity needs to be continued.